Application of Lean Management Principles on Improving Operational Efficiency in the Manufacturing Industry - Rizki, Dwiki Fatur (Universitas Syiah Kuala, 2023)
The manufacturing industry is currently increasingly faced with the challenge of increasing operational efficiency to maintain competitiveness. One approach that has proven effective in achieving this goal is the application of lean management principles. This article aims to dig deeper into how lean management principles can be applied in the context of the manufacturing industry to increase operational efficiency. The research method used is literature analysis, which searches literature through academic databases, online libraries and related literature sources. Literature selection will be carried out by paying attention to criteria such as relevance, author credibility, and year of publication to ensure the selection of up-to-date and high-quality literature. The results of this research include the application of lean management principles in the manufacturing industry, which positively impacts operational efficiency. By eliminating waste, encouraging employee participation, implementing JIT concepts, and leveraging technology, companies can achieve higher productivity goals, maintain a competitive advantage, and face market challenges more responsively. Thus, the manufacturing industry can benefit significantly from implementing lean management principles to remain competitive in a dynamic business environment. The success of this implementation depends on the company's commitment to changing work culture, engaging employees, and continuously seeking innovation to continuously improve operational efficiency.